Overnutrition of Ewe in Late Gestation and the Impact on Placental Efficiency and Lamb’s Performance - Sousa, Marco Antonio Paula de; Esteves, Sergio Novita; Daher, Luciara Celi Chaves; Gallo, Sarita Bonagurio; Pereira, Verônica Schinaider do Amaral; Fonseca, Jeferson Ferreira da; Silva, André Guimarães Maciel e; Brandão, Felipe Zandonadi; Oliveira, Maria Emilia Franco [UNESP]; Barreto, Andréa do Nascimento; Vergani, Gabriel Brun [UNESP]; Garcia, Alexandre Rossetto (MDPI, 2023)
The objective of the study was to evaluate energy or energy/protein supplementation in the ewe diet, in the last third of gestation, on maternal placental and endocrine characteristics, as well as its effects on the behavior of neonatal lambs and productive performance until weaning. A total of 128 ewes were used, and the experimental diet was fed from 100 days gestation until lambing, with the birth of 172 lambs. The ewes were distributed into three treatments: CTL (control, n = 43) with metabolizable energy (ME) and crude protein (CP) intake according to NRC (1985); ME (energy supplementation, n = 44) plus 21% ME; and MECP (energy/protein supplementation, n = 41) plus 26% ME and CP. Body weight, body condition score, serum hormone concentrations, placental characteristics, lamb performance and behavior, and production efficiency of the ewe from lambing to weaning were measured. ME and MECP ewes were heavier before (p = 0.006) and just after lambing (p = 0.002) and had higher serum triiodothyronine (p = 0.001) and cortisol (p = 0.004) concentrations on the day of lambing. ME ewes had higher placental efficiency (p = 0.036) and lower total cotyledon weight (p = 0.011). ME and MECP diets increased both lamb birth weight (p = 0.015) and weaning weight (p = 0.009). Production efficiency at birth and at weaning was not influenced (p > 0.05) by treatments. Lamb behavior was influenced by the ME and MECP diets, reducing the time to kneel (p ≤ 0.05), to try to stand (p ≤ 0.05), and the latency to stand (p ≤ 0.005). It is concluded that overnutrition in the last third of gestation was positive for the ovine production system, with improved production rates, hormonal profile, placental characteristics, and neonatal behavior.
Keywords: fetal development; fetal programming; maternal nutrition; Morada Nova; neonatal behavior; placenta